Pengaruh Penerapan Model Discovery Learning terhadap Hasil Belajar Siswa pada Pelajaran Fisika Kelas XII SMA - Nuryanti, Nuryanti (Universitas Tanjungpura, 2024)
This research is motivated by the limited number of students who struggle with understanding physics concepts in the Merdeka curriculum. For some students, physics is perceived as difficult due to the numerous formulas and calculations required, which negatively affects their cognitive learning outcomes. This is often caused by errors in selecting and implementing teaching models in the classroom. The aim of this study is to examine the effect of the discovery learning model on students' learning outcomes in physics for 12th-grade high school students. A quantitative experimental design was employed, involving one class of 35 students as the research subjects. Data collection occurred in two phases: a pre-test and a post-test. The pre-test was administered prior to the application of the discovery learning model, while the post-test was given after five sessions of instruction. Data analysis was conducted using the Wilcoxon test to determine significant differences between pre-test and post test results. The findings reveal a significant improvement in students' learning outcomes, with the average post-test score being higher than the pre-test score. The t-test yielded a p-value of less than 0.05, indicating that the application of the discovery learning model positively influences students' understanding of physics concepts. Based on these findings, it is recommended that teachers implement the discovery learning model in physics instruction to enhance student learning outcomes. This study contributes to the development of more effective teaching models in high school physics education.